A graduate recital in wind band conducting featuring analysis of: Eric Ewazen’s Symphony in brass, Shelley Hanson’s Dances with winds, and Paul Hindemith’s March from symphonic metamorphosis on themes by Carl Maria von Weber - Eaverson, Anna K. (Kansas State University, 2010)
This document was submitted to the Graduate School of Kansas State University as a partial requirement for the Master’s of Music Education degree. Enclosed is information pertaining to quality literature selection, a music education philosophy, theoretical and historical analyses, and rehearsal plans for the Graduate Conducting Recital of Anna K. Eaverson held on Wednesday, March 19, 2010. The analytical methods used in this document are based on the Blocher/Miles unit studies found in the Teaching Music Through Performance in Band series as well as macro-micro-macro score analysis. The selections analyzed using these methods include Symphony in Brass by Eric Ewazen, Dances with Winds by Shelley Hanson, and March from Symphonic Metamorphosis of Themes by Carl Maria von Weber by Paul Hindemith.
Keywords: Music; Ewazen; Hanson; Hindemith; Analysis; Eaverson; Education, Music (0522); Music (0413)